2019
DOI: 10.1080/00952990.2018.1559847
|View full text |Cite
|
Sign up to set email alerts
|

A quasi-experimental evaluation of marijuana policies and youth marijuana use

Abstract: Background: Marijuana use carries risks for adolescents' well-being, making it essential to evaluate effects of recent marijuana policies. Objectives: This study sought to delineate associations between state-level shifts in decriminalization and medical marijuana laws (MML) and adolescent marijuana use. Methods: Using data on 861,082 adolescents (14 to 18+ years; 51% female) drawn from 1999 to 2015 state Youth Risk Behavior Surveys (YRBS), difference-indifferences models assessed how decriminalization and MML… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Less attention has been given to the potential dynamic effects of MCLs. While the few studies ( n = 5) that modeled lagged policy effects tend to show no evidence that including lags alters their overall conclusions (31,37,38,41,44), the common methods for operationalizing delayed policy effects (i.e., linear effects from time of enactment, a set of lagged indicators) assume that implementation delays are homogeneous across heterogeneous policy designs and that the time course of such delays is uncorrelated with both the local and federal context (49), yet time series of medical cannabis patient take-up suggest this is likely not the case (15,50).…”
Section: Methodsmentioning
confidence: 99%
“…Less attention has been given to the potential dynamic effects of MCLs. While the few studies ( n = 5) that modeled lagged policy effects tend to show no evidence that including lags alters their overall conclusions (31,37,38,41,44), the common methods for operationalizing delayed policy effects (i.e., linear effects from time of enactment, a set of lagged indicators) assume that implementation delays are homogeneous across heterogeneous policy designs and that the time course of such delays is uncorrelated with both the local and federal context (49), yet time series of medical cannabis patient take-up suggest this is likely not the case (15,50).…”
Section: Methodsmentioning
confidence: 99%
“…A logistic regression model was fit for each of the outcomes of interest (physically active every day, optimal health, no school absences, no school-related problems) with the difference-indifferences estimator and fixed effects for year and state. 34,45 The parameter of interest is the differencein-differences estimator, 32 which is the interaction between a dummy variable indicating whether the state had a recess policy enacted by follow-up and a dummy variable indicating if the observation was from follow-up. The year fixed effect controls for any unmeasured trends in the outcomes over time while the state fixed effect controls for uncontrolled time-invariant differences between states.…”
Section: Discussionmentioning
confidence: 99%
“…Difference-in-differences analysis is used to estimate the causal impact of policy changes over time as a quasi-experimental alternative when randomized controlled trials are not feasible and works under the assumption that changes in an outcome would be identical between groups except for the impact of the policy implementation. 32 This approach has been used to estimate the effect of marijuana laws, 33,34 texting-while-driving bans, 35 and same-sex marriage laws. 36 Due to changes in the NSCH sampling strategy, survey mode, and other methodological changes, this analysis was limited to the 2003 to 2011/2012 period.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the years since Anderson et al reviewed data from 1990-2007, the advent of recreational marijuana laws has provided unprecedented access to cannabis. Previous research has attempted to measure the consequences of new cannabis liberalization efforts, [21] [22] [23] [24] [25] [26] [27] [28] but there are major disparities in the policy implementation dates among these studies. Recent research has confirmed that suicidal behaviors and other adverse mental health outcomes are correlated with marijuana use disorder (MUD), [29] [30] which can be exacerbated by increasing access to cannabis, [31] but these correlations are also prevalent with other substance use disorders.…”
Section: Introductionmentioning
confidence: 99%